Decrease in VEGF-Induced Pericardial Adhesion Formation Using Bevacizumab After Surgery. (February 2019) - Jelveh Moghaddam, Hosseinali; Aghajani, Marjan; Raeis-Abdollahi, Ehsan; Faghihi, Mahdieh; Dabbagh, Ali; Imani, Alireza
Objectives. Some degrees of postoperative cardiac adhesions occur in response to the first cardiac surgery in patients that may limit surgeons for subsequent operations and increase the risk of heart injury. In this article, we established a model of postoperative pericardial adhesions, and because vascular endothelial growth factor (VEGF) seems to initiate adhesion formation through inflammatory responses, we used an anti-VEGF antibody, that is, bevacizumab, to examine its effects on postoperative adhesion formation. Methods. Twenty Wistar rats were divided in 2 groups: control and bevacizumab. After chest opening, pericardial sac was opened and the heart was fully exposed. In the bevacizumab group, bevacizumab (2.5 mg/kg) was applied locally on the heart and then the chest was closed. The control group received saline solution as placebo. After 42 days, high-sensitivity C-reactive protein in peripheral blood was measured, and re-sternotomy was performed to measure severity of pericardial adhesions. Then, the hearts were collected from all rats to evaluate percentage of CD-31-positive cells (as a marker of angiogenesis) using immunohistochemical staining. Results . When the bevacizumab group was compared with the control group, we found that the mean score of adhesion (0.89 ± 0.38 vs 2.56 ± 0.41) and CD-31 expression (27.45 ± 3.75% vs 56.26 ± 1.98%) was decreased significantly after bevacizumab administration. However, we did not find any difference in high-sensitivity C-reactive protein levels of control and bevacizumab animals. Conclusion . In the current study, bevacizumab administration could effectively reduce adhesion formation after first sternotomy by preventing VEGF-induced angiogenesis through CD-31 downregulation.